Interstitial deletion of chromosome 10q23: a new case and review. - Farrell, S A (1993)
A new case of a deletion of 10q23 is described. Only two other deletions involving this region have been previously noted. A review of clinical features of these three children did not show a distinct pattern of dysmorphic features. Other interstitial deletions of 10q are listed.